2020
DOI: 10.30699/ijp.2020.111181.2188
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Phenotypic and Genotypic Characteristics of Carbapnemases-producing Enterobacteriaceae and Its Prevalence in a Referral Hospital in Tehran City

Abstract: KEYWORDS ABSTRACTEnterobacteriacea, drug resistance, microbial, polymerase chain reaction, primer,DNA, Gene Scan to discover online

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 48 publications
12
11
0
Order By: Relevance
“…The uppermost number of clinical isolates was collected from urine and sputum from the urinary tract infections and respiratory tract infections, respectively ( Table 1 ). These results are in agreement with those obtained by Jalalvand et al and Rimrang et al [ 7 , 28 ] who demonstrated that the most predominant Gram-negative bacilli were E . coli and K .…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…The uppermost number of clinical isolates was collected from urine and sputum from the urinary tract infections and respiratory tract infections, respectively ( Table 1 ). These results are in agreement with those obtained by Jalalvand et al and Rimrang et al [ 7 , 28 ] who demonstrated that the most predominant Gram-negative bacilli were E . coli and K .…”
Section: Discussionsupporting
confidence: 93%
“…with those obtained by Jalalvand et al and Rimrang et al [7,28] who demonstrated that the most predominant Gram-negative bacilli were E. coli and K. pneumoniae.…”
Section: Plos Onesupporting
confidence: 81%
See 3 more Smart Citations